2013
DOI: 10.1097/mjt.0b013e31824d5fbd
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulin Therapy for Calcium Channel Antagonist Poisoning

Abstract: The use of hyperinsulin therapy (HIT) in severe calcium channel antagonist (CCA) poisoning has become a more common therapy within the last decade. The objective of this study is to report 7 years of experience recommending HIT. This was a retrospective chart review utilizing our regional poison center (RPC) data from January 1, 2002, through December 31, 2008. All cases of CCA poisoning receiving HIT were searched. Endpoints included the number of CCA cases utilizing HIT, insulin dose, time of initiation of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 5 publications
(5 reference statements)
0
18
0
Order By: Relevance
“…High-dose insulin (intravenous (IV) bolus of 1.0 unit/kg followed by a 0.5–2.0 unit/kg/h infusion) showed an improvement in hemodynamics in one of two human observational studies, 20 , 21 all five human case series, 31–35 and all four animal studies 36–39 assessing that outcome, while a survival benefit was reported in animal studies. 36 , 39 Hypoglycemia (1 of 7 21 and 2 of 4 32 subjects) and hypokalemia (2 of 7 21 and 2 of 4 32 subjects) were reported as adverse effects in human cohort studies and case series, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…High-dose insulin (intravenous (IV) bolus of 1.0 unit/kg followed by a 0.5–2.0 unit/kg/h infusion) showed an improvement in hemodynamics in one of two human observational studies, 20 , 21 all five human case series, 31–35 and all four animal studies 36–39 assessing that outcome, while a survival benefit was reported in animal studies. 36 , 39 Hypoglycemia (1 of 7 21 and 2 of 4 32 subjects) and hypokalemia (2 of 7 21 and 2 of 4 32 subjects) were reported as adverse effects in human cohort studies and case series, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In animal models of verapamil and propranolol poisoning, HIET provided greater haemodynamic stability and survival compared to adrenaline or glucagon alone . In clinical cases, significant improvements in blood pressure (BP) and haemodynamic stability have been reported following poisoning in mono‐ and multidrug intoxications of verapamil, diltiazem, amlodipine, propranolol and other BBs . The onset of effect for HIET has been reported to occur between 15 min and 60 min after initiating therapy .…”
Section: High‐dose Insulin Euglycaemic Therapy (Hiet) In Bb and Ccb Pmentioning
confidence: 99%
“…Toxicity from cardiac drugs is associated with a large number of fatalities and significant morbidity ( 1 , 2 ). Furthermore, the advice given by poison control centers are often not followed ( 2 4 ). Consensus recommendations were published for out-of-hospital management of calcium channel blocker (CCB) ingestion ( 5 ), but recommendations for in-hospital care have not been systematically developed.…”
mentioning
confidence: 99%